2021
DOI: 10.1177/08862605211004108
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the Relationship Between Internalized Heterosexism and Psychological Intimate Partner Violence Perpetration: A Comparative Study of Lesbians and Bisexual Women in Turkey and Denmark*

Abstract: Psychological intimate partner violence (IPV) perpetration is not limited to heterosexual relationships and can affect all genders and sexual orientations, including lesbians and bisexual women (LB) both in Denmark and Turkey. Internalized heterosexism might be one of the factors increasing the risk of LB’s use of psychological IPV perpetration. However, it is still unclear how being LB in Turkey and Denmark interact in the internalized heterosexism and psychological IPV perpetration relationship. The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
2
15
0
2
Order By: Relevance
“…Bisexual participants involved in bisexual local or online community were at increased risk of IPV perpetration than those not involved in bisexual communities; however, in the path analysis, involvement in bisexual communities was not directly associated with IPV perpetration. Bi-negativity was positively associated with IPV perpetration Ummak et al ( 2021 ) Untangling the relationship between internalized heterosexism and psychological intimate partner violence perpetration: a comparative study of lesbians and bisexual women in Turkey and Denmark Turkey and Denmark N = 449, 418 (F), 10 (transgender), 12 (complex) Psychological IPV MMEA Scale Turkish participants were more likely to report all forms of psychological IPV perpetration (restrictive engulfment; denigration; hostile withdrawal; dominance/intimidation) than Danish participants. Bisexual participants were more likely to report all forms of psychological IPV perpetration, except for dominance/intimidation, than Lesbian participants.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Bisexual participants involved in bisexual local or online community were at increased risk of IPV perpetration than those not involved in bisexual communities; however, in the path analysis, involvement in bisexual communities was not directly associated with IPV perpetration. Bi-negativity was positively associated with IPV perpetration Ummak et al ( 2021 ) Untangling the relationship between internalized heterosexism and psychological intimate partner violence perpetration: a comparative study of lesbians and bisexual women in Turkey and Denmark Turkey and Denmark N = 449, 418 (F), 10 (transgender), 12 (complex) Psychological IPV MMEA Scale Turkish participants were more likely to report all forms of psychological IPV perpetration (restrictive engulfment; denigration; hostile withdrawal; dominance/intimidation) than Danish participants. Bisexual participants were more likely to report all forms of psychological IPV perpetration, except for dominance/intimidation, than Lesbian participants.…”
Section: Resultsmentioning
confidence: 98%
“…Only one study used probabilistic methods of sampling (Bogart et al, 2005 ). Most (39 studies) included self-identified LGB+ people (Ayhan Balik & Bilgin, 2021 ; Bacchus et al, 2017 ; Bartholomew et al, 2008a , b ; Bartholomew et al, 2008a , b ; Bogart et al, 2005 ; Chong et al, 2013 ; Derlega et al, 2011 ; Edwards et al, 2021 ; Finneran & Stephenson, 2014 ; Finneran et al, 2012 ; Fontanesi et al, 2020 ; Fortunata & Kohn, 2003 ; Gabbay & Lafontaine, 2017a ; Gabbay & Lafontaine, b ; Jacobson et al, 2015 ; Kelly et al, 2011 ; Lewis et al, 2017 ; Lewis et al, 2018 ; Longares et al, 2018a ; Longares et al, b ; Mason et al, 2016 ; Oringher & Samuelson, 2011 ; Pistella et al, 2022 ; Poorman & Seelau, 2001 ; Reuter et al, 2015 ; Schilit et al, 1990 ; Sharma et al, 2021 ; Stephenson & Finneran, 2016 ; Stephenson & Finneran, 2017 ; Stephenson et al, 2011a ; Stephenson et al, 2013 ; Swan et al, 2021 ; Taylor & Neppl, 2020 ; Telesco, 2003 ; Tognasso et al, 2022 ; Toro-Alfonso & Rodríguez-Madera, 2004 ; Turell et al, 2018 ; Ummak et al, 2021 ; Zavala, 2017 ). Regardless of their self-identified sexual orientation, 17 studies recruited participants on the basis of their involvement in a same-sex relationship (Balsam & Szymanski, 2005 ; Craft & Serovich, 2005 ; Craft et al, 2008 ; Edwards & Sylaska, 2013 ; Jones & Raghavan, 2012 ; Kahle et al, 2020 ; Kelley et al, 2014 ; Leone et al, 2022 ; Li et al,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations